2015
DOI: 10.1128/aem.04040-14
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Communities Respond to Long-Term CO 2 Elevation by Community Reassembly

Abstract: Fungal communities play a major role as decomposers in the Earth's ecosystems. Their community-level responses to elevated CO 2 (eCO 2 ), one of the major global change factors impacting ecosystems, are not well understood. Using 28S rRNA gene amplicon sequencing and co-occurrence ecological network approaches, we analyzed the response of soil fungal communities in the BioCON (biodiversity, CO 2 , and N deposition) experimental site in Minnesota, USA, in which a grassland ecosystem has been exposed to eCO 2 fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
26
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 72 publications
(98 reference statements)
8
26
1
Order By: Relevance
“…4). It has also been reported that sparsely distributed fungal species were reassembled into highly connected dense modules under long-term elevated CO 2 conditions (Tu et al, 2015).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…4). It has also been reported that sparsely distributed fungal species were reassembled into highly connected dense modules under long-term elevated CO 2 conditions (Tu et al, 2015).…”
Section: Discussionmentioning
confidence: 93%
“…Elucidating the complex interactions between bacterioplankton and other marine organisms under anthropogenic perturbations will increase our understanding of their impact in a holistic way. Previous studies using ecological network analysis showed that elevated CO 2 significantly impacted soil bacterial/archaeal community networks by decreasing the connections for dominant fungal species and reassembling unrelated fungal species in a grassland ecosystem (Tu et al, 2015). It was also reported using ecological network analysis that elevated pCO 2 did not significantly affect microbial community structure and succession in the Arctic Ocean, suggesting bacterioplankton community resilience to elevated pCO 2 (Wang et al, 2016).…”
Section: Introductionmentioning
confidence: 93%
“…Climate change can alter the community composition of ECMF by pushing fungi (Kipfer, Egli, Ghazoul, Moser, & Wohlgemuth, ) or their host plants (Fernandez et al, ) outside their ranges of physiological tolerance (Pickles, Egger, Massicotte, & Green, ). However, most studies to date that have examined ECMF or whole fungal community responses to simulated climate change have found fairly small effects (Fernandez et al, ; Mucha et al, ; Parrent, Morris, & Vilgalys, ; Tu et al, ) relative to natural changes in fungal communities observed along large natural gradients of temperature and precipitation (Jarvis, Woodward, Alexander, & Taylor, ; Nottingham et al, ; Peay et al, ; Talbot et al, ; Tedersoo et al, ). Yet, few datasets currently exist with spatial resolution necessary to make accurate predictions of ECMF response to climate change across relevant geographic regions (Mohan et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Estimates of global fungal species richness are in the millions (Taylor et al, 2014), while less than 2% have been formally described (Taylor et al, 2016). Long-term elevated CO 2 significantly decreased overall relative abundance of Ascomycota, but increased relative abundance of Basidiomycota (Tu et al, 2015). However, the Basidiomycetous fungi activities are reduced due to the anoxic upper layers in different types of peatland (Winsborough and Basiliko, 2010).…”
Section: Introductionmentioning
confidence: 95%
“…Glomeromycota and Neocallimastigomycota were present in logged-over peat at Cermat Ceria ( Figure 5b) and absent in the other peat ecosystems (Figures 5a,5c and 5d). Glomeromycota is the phylum for most arbuscular mycorrhizal fungi, which form symbioses with many herbaceous plants (Tu et al, 2015) found in logged-over forest at Cermat Ceria, the low relative abundance of Glomeromycota resulted from perennial plant species composition (Tu et al, 2015) such as in Maludam and matured oil palm at Durafaram and Naman. Glomeromycota is an important soil microbial group that affects multiple ecosystem functions and processes, including nutrient cycling, plant productivity and competition, and plant diversity (Alguacil et al, 2016).…”
Section: Phylogeny Of Eukaryotic Phylamentioning
confidence: 99%